REALITY OF GOVERNMENT ACTIVITES IN THE FIELD OF FARMER MANAGEMENT FOR AND RECLAIMING LANDS AND MAINTAINING THEIR SUSTAINABILITY IN BABIL PROVINCE - & Al-Anafee, Ismail (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The research aims at recognizing the reality of government activities in field of farmer management for the reclaimed lands and maintaining their sustainability in Babylon Province, by the following:- (Agricultural extension activities, Agricultural outfits activities, the activity of Bien Al-Nahreen Company for seeds products, Government loan activity, Water resources activity) and determine the level of framers application recommendation from applying the agricultural developments to the reclaimed lands, represented by (Irrigation treatment , fertilization treatment , Soil Conservation) and to maintain problems that farmers face in the operation of reclaimed land and sustainability in Babil province. The sub-district of Abu Gharaq in Babil Province had been chosen to conduct the research due to it has great area of reclaimed lands fully reclamation . The data were collected by survey and personal interview of haphazard class sample, proportionality of rate 12% of research population ,that comprise 1000 farmers with in fact of 120 of them To achieve the research targets a triple standard was prepared for the level description of the type of governments services provided to the farmers in this area, which is comprising of (66)items distributed into (5) aspects: (Agricultural extension activities, Agricultural outfits activities, the activity of Bien Al-Nahreen Company for seeds products, Government loan activity, Water resources activity). The grades of the standard ranges from (66-179) with average amounting at (124.81) grade, with standard deviation amounted at (23.55) grade, research sample were divided into three categories (low, Middle, high), the weights are (1, 2, 3) which were used respectively. A triple scale of the level of the farmers application and sustainability to recent technology was developed in the field of the reclaimed lands, consisting of (35) items, with grades ranging from (77-105)grade. Average of application recent technology is amounted at (48.3)grade, with deviation standard amounted at (8.5)grade. The results of the researcher reveal that the level of farmers’ application for the recommended agricultural recent technology in the field of management and sustainability for the reclaimed lands in Babil Province, generally, described as weak, while the level of farmers’ application for the recommended agricultural recent technology for each axis of management of reclaimed lands was as follows: Irrigation management described as middle, fertilization management and axis of soil conservation described as few. As for difficulties that face beneficiary peasant of reclaimed lands, the results showed variation of difficulties that researched faced, it related to productivity, extensional problems, and appliances difficulties, the researcher recommends the exigency of edification for the beneficiary farmers of reclaimed lands through prepare extensional and training specialized programs and activities under the supervision of extension staff of the province and the center.